Proposed Business Strategy for The Livestock Pharmaceutical Company In Indonesia - Iskandar, Bachtiar; Wandebori, Harimukti (Journal Research of Social Science, Economics, and Management, 2025)
Indonesia’s poultry industry plays a vital role in national food security and economic growth, yet it faces challenges such as oversupply, declining demand, and increasingly stringent government regulations. PT MAS, a key player in the veterinary pharmaceutical and vaccine market, has experienced stagnating growth and intensified competition from both local and international firms. This study investigates the strategic competitiveness of PT MAS by analyzing external and internal factors using the Industrial Organization (I/O) model, PESTEL analysis, Porter’s Five Forces, and value chain analysis. A qualitative case study method was employed, drawing from primary data (focus groups, executive workshops) and secondary sources (industry reports, company documents). The findings highlight critical issues, including reduced market share in key product segments, disruptive technology trends such as in-ovo vaccination, and regulatory shifts away from antibiotics. Using a scenario planning approach, the study proposes sustainable strategies aligned with external environmental changes and internal capability development. A strategic map and balanced scorecard were developed to monitor and evaluate performance. The study concludes that PT MAS’s future competitiveness depends on strategic agility, technology investment, regulatory alignment, and the shift toward herbal and residue-free solutions. This research contributes to the body of knowledge on strategic management in emerging markets and provides actionable insights for firms operating in complex, regulated agribusiness environments.